Clinical researchThe analysis of prognostic factors affecting post-radiation acute reaction after conformal radiotherapy for non-small cell lung cancer - Spych, Michał; Gottwald, Leszek; Klonowicz, Małgorzata; Biegała, Michał; Bibik, Robert; Fijuth, Jacek (Archives of Medical Science, 2010)
Introduction : The aim was to evaluate the risk of acute side effects in the lung after 3-dimensional conformal radiotherapy (3D-CRT) in patients treated for non-small cell lung cancer (NSCLC). An attempt was made to single out clinical factors and factors related to treatment technique which may induce acute post-radiation pneumonitis. Material and methods : The analysis concerned 34 consecutive patients who underwent radical radiation therapy for NSCLC. Intensity of early toxicity was evaluated using modified RTOG/EORTC toxicity score. The endpoint for this analysis was the occurrence of radiation pneumonitis of grade 2 or higher. Factors related to treatment techniques were included in the statistical analysis. Results : Fifty-three percent of patients included in the study suffered from acute post-radiation pneumonitis. The results of the study revealed the existence of lung tissue sensitivity to low doses of ionizing radiation. The multivariate analysis showed that total lung volume receiving a low dose of 10 Gy increased the risk of post-radiation pneumonitis (p = 0.01). Conclusions : Acute post-radiation pneumonitis was a relevant clinical problem in patients who underwent radical radiotherapy for non-small cell lung cancer. The lung volume receiving a dose of 10 Gy was the most important dosimetric factor which influenced the post-radiation acute pneumonitis.